Metabolic and developmental consequences of continuous vs. refreshed culture of bovine embryos in BBH7 media - Wills, Jennifer Rose (2013)
In vitro production of bovine embryos is an effective tool for quickly and efficiently improving herd genetics. Previously, detrimental effects of continuous culture (to day 7) on embryonic development have been reported due to a toxic build-up of ammonia. BBH7 is a serum-free in vitro culture media that has been specifically developed to improve the yield and cryo-tolerance of bovine embryos. Currently, bovine embryos are cultured continuously in BBH7 and it is the aim of this thesis to determine whether this culture system is detrimental to embryo development.